A new configuration of a printed diplexer designed for DCS and ISM bands - H. Setti; J. Zbitou; A. El Hamichi; A. Tribak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This work presents a new study on the design of a microstrip diplexer configuration optimized and validated for ISM and DCS frequency bands. The achieved structure is based on microstrip technology, the goal was to design two printed bandpass filters one for ISM band and the other one for DCS frequency band.The two microstrip filters are associated by using a T-junction which permits to validate a diplexer in the frequency bands DCS-Band receiver [1.74–2 GHz] and ISM-Band transmitter [2.3–2.55 GHz]. The whole size of the final circuit is 130x50 mm2. After the validation of the proposed diplexer into simulation we have fabricated and tested it by using VNA which permits to have a good agremment between simulation and measurements.